Pathways toward Change: Ideologies and Gender Equality in a Silicon Valley Technology Company. Issue 1 (February 2020) - Wynn, Alison T.
Companies have devoted significant resources to diversity programs, yet such programs are often largely ineffective. Cultivating an organizational commitment to diversity is critical, but scholars lack a clear understanding of how top executives conceptualize change. In this article, I analyze data from a year-long case study of a Silicon Valley technology company implementing a gender equality initiative. The data include 50 in-depth interviews and observation of 80 executive meetings. I pay special attention to longitudinal interviews with 19 high-level executives and explore how their ideologies about inequality affected their change efforts. I find that executives tend to favor individualistic and societal explanations of gender differences and inequality, and these explanations correspond with change efforts focused mainly on altering individuals or affecting external communities. Executives rarely engaged in attempts to change the organization structurally. Thus, the implementation of gender equality remains limited by top executives' ideas and assumptions about the sources of inequality.